Rancangan Instrumen Penilaian Kinerja Pegawai Pelaksana Marketing di Unit Pelaksana Teknis Pengelolaan Sampah Kota Bandung - Indah Ramadhani Indarwati; Nefi Aris Ambar Asmara; Teni Listiani (Jurnal Media Administrasi Terapan, 2022)
Performance assesment is an important process in human resource management. As with the times and changes in policy, performance assesment instruments are adjusted to the performance goals of the organization. The purpose of this study was to analyze and identify the indicators used to assess the performance of marketing implementers, to create marketing implementer instruments in accordance with organizational needs and marketing performance assesment mechanisms at UPT Pengelolaan Sampah DLHK Kota Bandung. We used qualitative method with a descriptive approach in this study. Data collection techniques were carried out through interviews with six informants accompanied by observations and literature studies to identify, select and develop performance indicators. In addition to collecting information for the preparation of indicators, it is sourced from applicable regulations, assignment and previous research. The results of the study stated that the instruments has been used so far need updating because several things are no longer relevant. The improvements provided by the new instrument including implementation time with a shorter working period (every three months), the assessment is done by superiors and fellow colleagues, using indicators based on the job descriptions, and more specific. To reduce assessment bias, training for assessment can be carried out which includes assesment in decision making to maintain neutrality and objectivity, as well as assistance from human resouce department to make decision.